Decrease in Resident Arthroscopic Case Volume After 2013 Implementation of Minimum Case Requirements - Samir Sabharwal, M.D., M.P.H; Gregory R. Toci, B.S; Adam A. D'Sa, B.A; Suresh K. Nayar, M.D; Dawn M. LaPorte, M.D (Elsevier, 2021)
Purpose: To analyze graduating U.S. orthopaedic resident case logs to determine temporal trends in knee and shoulder arthroscopic case volumes, as well as changes in the variability of caseload volumes since the implementation of Accreditation Council for Graduate Medical Education (ACGME) minimum case requirements ("case minimums") in 2013. Methods: We abstracted ACGME-published case log data for all U.S. orthopaedic surgery residents who graduated from 2007 to 2013 (before implementation of case minimums) and from 2014 to 2019 (after implementation). Using a case-control study design, we compared mean numbers of arthroscopic knee and shoulder cases reported per resident between the 2 time periods by using unpaired 2-tailed t tests. P values < .05 were considered significant. Results: The mean number of arthroscopy knee cases reported by residents decreased from 164 before implementation of case minimums to 107 after implementation (P < .001). The mean number of shoulder cases decreased similarly from 98 to 66 (P < .001). Among residents with caseload volumes in the 90th percentile ("high-volume caseloads") the decrease was greatest, with 38% fewer knee cases and 41% fewer shoulder cases logged. The ratio of the number of cases in the 90th percentile of caseload to the number in the 10th percentile decreased significantly after implementation of case minimums (P < .001). Conclusions: After implementation of ACGME case minimums in 2013, the numbers of arthroscopic knee and shoulder cases reported by graduating U.S. orthopaedic surgery residents decreased significantly. The disparity between the number of cases that constitutes a high-volume caseload and the number that constitutes a low-volume caseload narrowed, suggesting greater uniformity in resident exposure to these procedures across training programs. Level of Evidence: Level III, retrospective comparative study.